Prevalence and Antifungal Susceptibility of Candida species from patients attending Rivers State University Teaching Hospital, Nigeria - D. N Girah.; N. P Akani.; O Aleruchi. (International Journal of Clinical Microbiology, 2024)
The development of medical therapy and patients profile has led to a rise in the incidence of nosocomial fungal infection. The frequency of candidiasis has surged worldwide, and the prevalent of healthcare diseases are now Candida species. Candida species causes a range of human infections known as Candidiasis. The non-albicans Candida (NAC) species have recently superseded Candida albicans as significant opportunistic pathogens. The study was conducted to determine the prevalence and antifungal susceptibility of Candida species isolated from various Clinical samples in Rivers State University Teaching Hospital, Port Harcourt, Nigeria. A total of 206 clinical specimens from male and female patients of all ages were sampled in the Department of Microbiology, Rivers State University Teaching Hospital, Port Harcourt, to investigate suspected Candida infections. The isolation and identification of Candida species was done by culture on SDA, Gram stain, sugar fermentation and phylogenetic profiling. Antifungal susceptibility pattern was done by Disc Diffusion method using Fluconazole, Ketoconazole, Miconazole, Nystatin and Itraconazole. The results showed that out of 206 specimens, 44 isolates (21.4%) were identified, with the majority (56.82%) from high vaginal swabs (HVS), followed by urine (31.82%) and oral swabs (11.36%). The age of patients ranged from four months to 73 years giving a Mean Age 1.86+ 0.344, with females (85.4%) outnumbering males (13.6%). Prevalence of Candida spp revealed Candida albicans (50%), Candida krusei (18.2%), Candida parapsilosis(11.4%), Candida glabrata and Candida tropicalis (9.1%) respectively and Candida pelliculosa (2.2%), with C. albicans being the most prevalent. The antifungal susceptibility testing among the azoles showed that Fluconazole (79.5%) and Ketoconazole (77.3%) were most sensitive agents against isolates from HVS, urine and oral swabs respectively and Itraconazole (34.1%) was most resistant especially to those from oral swabs. This study highlights the increasing prevalence of NAC species over Candida albicans and the growing resistance of Candida isolates to commonly used antifungal drugs. Diagnosis of these species of Candida and sensitivity to antifungal agents are critical components to treatment, particularly for patients with severe underlying illnesses who are hospitalized.
Keywords: Candida species